Taxonomy and phylogeny of Begonia L. (Begoniaceae) in Laos I: B. luangprabangensis, a new species from karst limestone in northern Laos, with notes on the distribution of B. demissa - Phonepaseuth, Phongphayboun (Phytotaxa, 2026)
Begonia luangprabangensis Phonep., a new species from Luang Prabang Province, northern Laos, is described and illustrated, with its taxonomic placement in Begonia sect. Diploclinium supported by molecular phylogenetic analyses. The new species is morphologically similar to B. henryi Hemsl. in having a tuberous base, two tepals in both staminate and pistillate flowers, and an asymmetric androecium, but differs in having 3-winged fruits equal to subequal with thicker ovary walls (vs. unequal with thin walls), and bilamellate placentation (vs. undivided). It is also shares several characters with B. murina Craib including a tuberous habit, short stem, pistillate flower with two tepals and a 3-locular ovary. It differs from B. murina, however, by having staminate flowers with two tepals (vs. four), androecium asymmetric like a bunch of bananas (vs. androecium symmetric), and a trigonous, horned and berry-like fruit (vs. a dry fruit with 3 subequal wings). In addition, the known distribution of B. demissa Craib in Laos and its phylogenetic position are presented. A checklist of Begonia species occurring in northern Laos is also provided.